Age-Group Differences in Reactive Strength and Measures of Intra-day Reliability in Female International Footballers - Brian Doyle; Declan Browne; Dan Horan (International Universities Strength and Conditioning Association, 2021)
The aim of this present study was to compare the reactive strength index (RSI) characteristics and trial to trial reliability of U17, U19 and Senior female international soccer players. Fifty - seven elite female soccer player participated in the study, (age:  18.1 + 3.1 years; height: 167.5 + 6.3 cm; weight: 61.84 + 7.7 kg). Participants performed 3 maximal repetitions of the 10/5 repeated jump test (10/5RJT) following a specific warm-up and familiarisation protocol. Senior players possessed higher levels of RSI with large effect size present when compared with the U17 (P= 0.043, ES = .97) and U19 (ES = 0.85) age groups. Trivial differences (ES = 0.17) in RSI existed between the U17 and U19 age categories. Trial-to-trial analyses demonstrated 10/5 RJT RSI to possess adequate levels of reliability with a range of mean coefficients of variance (CV) of 3.1 - 7.3 %   and intraclass correlation (ICC) between 0.95 - 0.98 present across all three age groups. However, large variations in the between - athlete CV for RSI were revealed ranging from 1 - 27 %, 0.4 - 10.3%, and 1 - 7 % for U17, U19 and senior age groups respectively. These results suggest that age group can distinguish reactive strength capabilities. In addition, female international footballers with higher levels of RSI appear to produce more reliable measures of RSI via the 10/5 RJT.